The short-horned grasshoppers (Acrididae and Pyrgomorphidae: Orthoptera) of Karnataka, India: A checklist and distribution data - Loka Mounika; Rajamani Swaminathan; Chicknayakanahalli M. Kalleshwaraswamy (Environment Conservation Journal, 2024)
Short-horned grasshoppers’ checklist is presented here. In the present study, the inventory was created using data from a survey conducted in various districts of Karnataka between 2019-2021, including Chikkamagaluru, Dakshina Kannada, Davanagere, Hassan, Kodagu, Shivamogga, Udupi, Uttar Kannada and orthopteran collections at the Insect Systematics Laboratory, Department of Entomology, KSNUAHS, Shivamogga and literature published to date from various parts of Karnataka. A total of 101 species/subspecies belonging to 66 genera, 15 subfamilies and two families i.e., Acrididae and Pyrgomorphidae were reported. Several species were recorded for the first time from the districts investigated, including 9 in Chikkamagaluru, 4 in Dakshina Kannada, 1 each in Hassan and Kodagu, 3 in Shivamogga, 9 in Udupi and 1 in Uttar Kannada. This is the first-ever checklist featuring distribution records for short-horned grasshoppers in Karnataka and is updated with the Orthoptera species file online. The index may help for future taxonomic diversity studies of grasshoppers of Karnataka